New species of Caromiobenella Jeon, Lee & Soh, 2018 (Crustacea, Copepoda, Monstrilloida) from Chuja Island, Korea - Donggu Jeon; Wonchoel Lee; Ho Young Soh (ZooKeys, 2019)
Male monstrilloid copepods belonging to the genus Caromiobenella Jeon, Lee & Soh, 2018 were collected from Chuja Island, Jeju, Korea, using a light trap. This paper describes a new species, Caromiobenella ohtsukai sp. n., based on the display of reduced, knob-like fifth legs on the ventral side of the first urosomal somite. A unique combination of male genitalia features and number of caudal setae further confirms its specificity. Molecular analysis based on two partial gene sequences of mitochondrial cytochrome c oxidase subunit I (mtCOI) and 28S ribosomal RNA (28S rRNA) also supports the designation of this species by showing a relevant divergence from known congeners. Caromiobenella ohtsukai sp. n. is the ninth member of this genus and also the ninth monstrilloid reported from Korea.